2016
DOI: 10.1080/13803395.2016.1204991
|View full text |Cite
|
Sign up to set email alerts
|

Intrusions and provoked and spontaneous confabulations on memory tests in Korsakoff’s syndrome

Abstract: Introduction: Intrusions on verbal memory tests have been used as an index for clinical confabulation. Severe memory impairments in combination with executive dysfunction have been suggested to be the underlying mechanism of confabulation, but to date, this relation is unclear. The aim of this study was (a) to examine the relation between (different types of) intrusions and confabulations in a large sample of confabulating patients with Korsakoff's syndrome (KS) and (b) to investigate whether different measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
2
7
0
3
Order By: Relevance
“…Intrusions in memory testing [provoked confabulations ( 44 ), simple provoked confabulations ( 45 ), memory-recall-provoked confabulations ( 46 )] may occur in normal controls ( 47 ), but they are rare ( 48 , 49 ), unless after a retention interval longer than the one used in clinical assessment ( 44 ). Patients with alcoholic KS commonly produce intrusions ( 23 , 33 ), which are similarly to our patients semantic ( 23 ). In previous studies of neuropsychologically documented non-alcoholic KS, intrusions have been reported in five cases, including the three in our recent report ( 15 , 20 , 50 ), whereas they were absent in one case ( 51 ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Intrusions in memory testing [provoked confabulations ( 44 ), simple provoked confabulations ( 45 ), memory-recall-provoked confabulations ( 46 )] may occur in normal controls ( 47 ), but they are rare ( 48 , 49 ), unless after a retention interval longer than the one used in clinical assessment ( 44 ). Patients with alcoholic KS commonly produce intrusions ( 23 , 33 ), which are similarly to our patients semantic ( 23 ). In previous studies of neuropsychologically documented non-alcoholic KS, intrusions have been reported in five cases, including the three in our recent report ( 15 , 20 , 50 ), whereas they were absent in one case ( 51 ).…”
Section: Discussionsupporting
confidence: 71%
“…Intrusions were defined as false words in the Hopkins Verbal Learning Test–Revised (HVLT-R) and false statements in the Wechsler Memory Scale–III (WMS-III). Intrusions semantically related to the presented material were considered semantic ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, no significant correlation was found between the NVCL-20 and the CVLT intrusions variable, questioning the previous use of this as an index of confabulation (e.g., Schnider et al, 1996). Rensen et al's (2017) findings corroborate this concern, finding no correlation between spontaneous and provoked confabulation as measured by the NVCL-20 and the total number of intrusions on the CLVT. However, small but non-significant correlations were found between unrelated intrusions and both forms of confabulation ( r = 0.20 for both analyses), suggesting intrusions unrelated to the information learnt may be more closely associated with confabulations than those related.…”
Section: Resultsmentioning
confidence: 88%
“…The use of the Intrusions variable of the CVLT as an index of confabulation is questionable. The findings from Rensen, Oosterman, van Damme, Griekspoor, Wester and Kopelman (2015, 2017) suggest intrusions, while related to confabulations, may be distinct phenomena. The NVCL-20 observational scale for measuring confabulatory behavior appears more suitable for assessing confabulation in those with ARCI, demonstrating superior psychometric properties to other measures used for this purpose.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation